Mode of action of claudin peptidomimetics in the transient opening of cellular tight junction barriers. (June 2015) - Staat, Christian; Coisne, Caroline; Dabrowski, Sebastian; Stamatovic, Svetlana M.; Andjelkovic, Anuska V.; Wolburg, Hartwig; Engelhardt, Britta; Blasig, Ingolf E.
Abstract: In epithelial/endothelial barriers, claudins form tight junctions, seal the paracellular cleft, and limit the uptake of solutes and drugs. The peptidomimetic C1C2 from the C-terminal half of claudin-1's first extracellular loop increases drug delivery through epithelial claudin-1 barriers. However, its molecular and structural mode of action remains unknown. In the present study, >100 μM C1C2 caused paracellular opening of various barriers with different claudin compositions, ranging from epithelial to endothelial cells, preferentially modulating claudin-1 and claudin-5. After 6 h incubation, C1C2 reversibly increased the permeability to molecules of different sizes; this was accompanied by redistribution of claudins and occludin from junctions to cytosol. Internalization of C1C2 in epithelial cells depended on claudin-1 expression and clathrin pathway, whereby most C1C2 was retained in recyclosomes >2 h. In freeze-fracture electron microscopy, C1C2 changed claudin-1 tight junction strands to a more parallel arrangement and claudin-5 strands from E-face to P-face association – drastic and novel effects. In conclusion, C1C2 is largely recycled in the presence of a claudin, which explains the delayed onset of barrier and junction loss, the high peptide concentration required and the long-lasting effect. Epithelial/endothelial barriers are specifically modulated via claudin-1/claudin-5, which can be targeted to improve drug delivery.